O poszukiwaniu funkcji użyteczności gospodarstwa domowego - Gąsiorowski, Paweł; Kuszewski, Tomasz (On Searching the Houshold Utility Function, 2007)
The paper presents an estimation of household utility function elasticity with linear regression, power regression, and with neural networks. The results obtained by the two methods are not similar, however the neural networks allow for more flexibility in defining relationship between the variables influencing preferences of households. The elasticities were estimated on the panel dataset from over 4ths households budgets from year 2002
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 65-74